Impact of coronavirus disease-19 pandemic on pediatric vaccine clinical trials - Neeta Hanumante; Dipali Desale (Indian Journal of Child Health, 2021)
Introduction: The coronavirus disease (COVID)-19 pandemic has affected nearly every facet of life, including clinical research, and has had an adverse and extensive impact on clinical trials including pediatric vaccine trials. Across the globe, countries implemented a variety of restrictions to people’s everyday lives, which have substantially impacted the ability to conduct pediatric vaccine trials. Objectives: The objectives of the study were to assess the impact of the COVID-19 pandemic on enrollment and follow-up of clinical trial participants in pediatric vaccine clinical trials and simultaneously to explore various strategies used for overcoming these challenges during the COVID-19 pandemic period. Materials and Methods: Data of 10 pediatric vaccine clinical trials were obtained from the clinical trial records of the Clinical Research Unit. The number of subjects enrolled, number of study dropouts, protocol deviations, and reasons for participant dropout/deviations were recorded from these pediatric vaccine clinical trials carried out before and during the COVID-19 pandemic period from March to December 2020. These metrics were then compared with their counterparts recorded during our study to statistically assess the impact of the COVID-19 pandemic. Various factors which have affected the recruitment and follow-up in pediatric vaccine clinical trials and various strategies used to curtail subject dropout and protocol deviations during COVID-19 pandemic were studied in detail. Results: The primary and most visible impact of the COVID-19 pandemic was that protocol deviations and study dropouts were significantly higher for the trials conducted during COVID-19 pandemic period. The difference between proportion of protocol deviations and study dropouts in the pediatric vaccine clinical trials conducted during pandemic and trials conducted before pandemic was statistically significant (<0.05). The recruitment for ongoing trials was also adversely affected. Conclusion: At our site, the COVID-19 pandemic has affected the conduct and recruitment of pediatric vaccine trials markedly in an adverse manner. The protocol deviations and study dropout were significantly higher during the COVID-19 pandemic period. To counter these effects and still have the trials retain their effectiveness, we found that it is essential to implement measures and strategies for maintaining compliance and safe conduct of clinical trials. Adoption of telemedicine may offer promise in terms of a way forward for conducting clinical trials.